Peroneal nerve palsy after compression stockings application - Jun Hyun Kim; Won Il Kim; Ji Yeon Kim; Won Joo Choe (Saudi Journal of Anaesthesia, 2016)
Peroneal nerve palsy can be caused by various etiology. We report unilateral peroneal nerve palsy after compression stockings application. A 64-year-old man underwent off-pump coronary bypass graft. Surgeon did not use saphenous vein for the bypass graft. Sedation was stopped after 3 h postoperative. After 16 h, for prophylaxis of deep vein thrombosis, knee-high elastic stocking was applied. After 1 h, he took off right stocking because of numbness but left stocking was kept. After 24 h postoperative, (8 h after stocking application) patient complained suddenly left foot drop. Manual muscle test revealed 0/5 of ankle dorsiflexion, ankle eversion, and toe extension. Sensory was decreased to 70% in lower half of anterolateral aspect of tibia, foot dorsum, and toes. Foot drop and sensory abnormality decreased in 3 weeks. Cardiac surgery patients already have many risk factors for peripheral neuropathy. Clinicians should be careful when applying stockings on those patients.